2010
DOI: 10.1176/appi.ajp.2009.09091261
|View full text |Cite
|
Sign up to set email alerts
|

Do Treatment Improvements in PTSD Severity Affect Substance Use Outcomes? A Secondary Analysis From a Randomized Clinical Trial in NIDA's Clinical Trials Network

Abstract: Objective-The purpose of the analysis was to examine the temporal course of improvement in Posttraumatic Stress Disorder (PTSD) and substance use disorder symptoms among women in outpatient substance abuse treatment.Method-Participants were 353 women randomized to 12 sessions of trauma-focused or health education group treatment. PTSD and substance use assessments were conducted during treatment and at 1-week, 3-, 6-, and 12-months post treatment. A continuous Markov model was fit on participants' four defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
207
2
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 276 publications
(235 citation statements)
references
References 20 publications
(11 reference statements)
21
207
2
2
Order By: Relevance
“…It is important to note, however, that studies examining the temporal sequencing of changes in PTSD and substance dependence symptoms have shown that improvements in PTSD symptoms are associated with subsequent improvements in substance dependence, but the reciprocal relationship is not observed. 31,32 These findings highlight the importance of treating PTSD to improve substance dependence outcomes for individuals with this comorbidity.…”
Section: Commentmentioning
confidence: 94%
“…It is important to note, however, that studies examining the temporal sequencing of changes in PTSD and substance dependence symptoms have shown that improvements in PTSD symptoms are associated with subsequent improvements in substance dependence, but the reciprocal relationship is not observed. 31,32 These findings highlight the importance of treating PTSD to improve substance dependence outcomes for individuals with this comorbidity.…”
Section: Commentmentioning
confidence: 94%
“…Interestingly, the elevated risk of developing secondary psychiatric diagnoses disappears with the remission of PTSD symptoms [13]. In addition, in patients with PTSD and comorbid substance abuse, the treatment of PTSD improves symptoms of substance abuse, but treatment directed toward substance abuse does not appear to ameliorate PTSD symptoms [15]. …”
Section: Introductionmentioning
confidence: 99%
“…These changes include reinstatement to drug-related cues and a persistent drugseeking response following cue-induced reinstatement. Clinical studies have shown that trauma-focused treatments are significantly more effective at improving SUDs in individuals with a comorbid PTSD diagnosis (Hien et al 2010), suggesting that our preclinical approach could be used in situations that may better model the clinical condition (Hariri and Holmes 2015). Because this model involves measurable behavioral responses in the stress-associated context (freezing) and the drug-associated context (drug-seeking), it can serve as a tool for understanding the relation between learned fears and substance abuse, as well as the potential to test novel therapeutic agents designed to weaken fear and attenuate reinstatement in the comorbid condition.…”
Section: Discussionmentioning
confidence: 99%